AKT-targeted anti-inflammatory activity of the methanol extract of Chrysanthemum indicum var. albescens. (6th April 2017) - Yang, Woo Seok; Kim, Donghyun; Yi, Young-Su; Kim, Ji Hye; Jeong, Hye Yoon; Hwang, Kyeonghwan; Kim, Jong-Hoon; Park, Junseong; Cho, Jae Youl
Abstract: Ethnopharmacological relevance: Wild chrysanthemum ( Chrysanthemum indicum ) is one of well-known medicinal plants traditionally used in Korea and China. As a variant of wild chrysanthemum, white wild chrysanthemum ( Chrysanthemum indicum var. albescens) is also ethnopharmacologically applied to treat various symptoms such as inflammatory diseases. Aim of study: Although the anti-inflammatory activity of Chrysanthemum indicum has been reported, the anti-inflammatory activity and underlying molecular mechanism of white wild chrysanthemum are poorly understood. Materials and methods: The effects of Chrysanthemum indicum var. albescens methanol extract (Civ-ME) on the production of inflammatory mediators, expression of pro-inflammatory genes, cell viability, and the activities of intracellular signaling molecules and transcription factors were investigated in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Results: Civ-ME suppressed the production of both nitric oxide (NO) and prostaglandin E2 (PGE2 ) without cytotoxicity in LPS-stimulated RAW264.7 cells. Civ-ME was found to reduce the mRNA levels of inflammatory genes such as inducible NO synthase (iNOS) and tumor necrosis factor (TNF)-α and reduced NF-κB-mediated transcriptional activation. Civ-ME inhibited the nuclear translocation of NF-κB (p65 and p50), and its upstream signaling composed of IκBα and IKKα/β. An NF-κB luciferase reporter gene assay and an in vitro kinase assay confirmed that AKT1 and AKT2 might be direct pharmacological targets of Civ-ME. In addition, luteolin was identified by HPLC analysis as the main active pharmacological components of Civ-ME. Conclusion: Civ-ME exerts an anti-inflammatory effect by targeting AKT1 and AKT2 in the NF-κB signaling pathway in macrophage-mediated inflammatory responses. Graphical abstract: